Pengaruh Kualitas Produk, Kualitas Layanan Dan Citra Merek Terhadap Kepuasan Konsumen Pada CV.Arsana Sentosa - Fauzy, Syafira Adinda; Suherman, Enjang (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of product quality, service quality and brand image on consumer satisfaction at CV. Arsana Sentosa, manufacturer of ASTA brand fire extinguishers in Karawang. Using descriptive quantitative methods and multiple linear regression analysis, this research found that of the three independent variables tested, only brand image had a significant influence on consumer satisfaction. Product quality and service quality, although having a positive relationship, do not show a statistically significant effect. These results indicate that a strong brand image plays a more important role in increasing consumer satisfaction than product and service quality. Therefore, CV. Arsana Sentosa is advised to focus on strategies to improve its brand image through effective marketing campaigns, product innovation and improving service quality. With this approach, companies can increase consumer satisfaction and maintain a competitive position in the market.